2021
DOI: 10.20944/preprints202103.0704.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Telenursing as a New Nursing Paradigm in the 21 Century: A Literature Review

Abstract: Nursing is a part of health services that serves individuals, groups and communities. In this 21st century the need for nursing services has changed rapidly and in a complex manner. Physical limitations, is on should to be considered, while the implementation and maintenance of patient-centered service infrastructure still have to be recked. The aim of this literature review is to identify the role of telenursing in nursing services for patients. This language method uses literature reviews which are summaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
9
0
3
Order By: Relevance
“…The same thing was also expressed by participants that the cost of buying data and credit is also sometimes a problem for participants who do not use it. The results of the review of 10 articles found that the form of nursing services with telenursing proves that distance services can save time and funding but for unsatisfactory quality related to the implementation of nursing services (Afik & Pandin, 2021). Knowledge and communication skills via telephone should be improved according to the needs of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The same thing was also expressed by participants that the cost of buying data and credit is also sometimes a problem for participants who do not use it. The results of the review of 10 articles found that the form of nursing services with telenursing proves that distance services can save time and funding but for unsatisfactory quality related to the implementation of nursing services (Afik & Pandin, 2021). Knowledge and communication skills via telephone should be improved according to the needs of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Con todo, la teleenfermería es una solución para responder a estos desafíos y necesidades de eficiencia a distancia y limitaciones de costos (27) . Asimismo, tiene muchos beneficios en la situación actual y es una medida práctica y confiable en la planificación e implementación efectiva de intervenciones que tienen un impacto positivo en la salud pública (28,29) , por tanto, la teleenfermería debe ser incorporada en la formación universitaria e impulsada a través de cursos y seminarios (30) .…”
Section: Discussionunclassified
“…However, not many have seen the effectiveness of online nursing care. Online nursing care has become commonplace in nursing and provides positive results for both families and clients (Huter et al, 2020)Various types of online nursing care such as telenursing (Afik & Pandin, 2021;Bartz, 2020;Boro & Hariyati, 2019) have been shown to improve the physical and mental conditions of clients and caregivers. The provision of online therapy can be an alternative for providing nursing care to hypertensive clients and their families, especially if families and clients experience obstacles in accessing health services face-to-face during the COVID-19 pandemic.…”
Section: Changes In Medication Adherencementioning
confidence: 99%